Understanding Information Seeking Behavior of Indonesian Postgraduate Students in Malaysian Universities: An Empirical Study - Subhan, Muhammad; Abdul Ghani, Ahmad Bashawir (Jurnal ILMU KOMUNIKASI, 2008)
Abstract : This study investigates Indonesian postgraduate student’s experience at the pre-sessional program of the process of seeking information and the strategies they used throughout the process. The objective is to understand their information seeking behavior particularly academic-related information in order to improve the effectiveness of educational communication in Malaysia higher institutions. Two research questions are addressed: what experiences do pre-sessional students face in the process of information seeking that can be articulated and described? What stages do pre-sessional students experience in the process of information seeking construction? Using the qualitative method, the study found that the pre-sessional students have different patterns in the constructive process of information seeking in two different groups i.e. writing and reading classes. Six stages and four stages of the search process were identified respectively for the two groups.